Adding practical experience to computer security course. Issue 2 (7th December 2017) - Stanisavljevic, Zarko; Vuletic, Pavle
Abstract: Computer security has become one of the core areas according to IEEE Computer Society and ACM Joint Task Force curriculum guidelines for undergraduate degree programs in computer engineering and software engineering. At the University of Belgrade, School of Electrical Engineering there is a course called Computer Security that is taught to software engineering and computer engineering students for the past 9 years. During this time a significant change was made to the course regarding the level of practical students' work. Several factors initiated the change: the recommendations in the curriculum guidelines, the analysis of the students' success at the exams, and the students' opinion. The impact of gradual transition from no practical activities at all to laboratory exercises and practical project at the course are described in this paper. Results show that the introduction of laboratory exercises at the course helped students to better understand some of the core areas and that the introduction of practical project increased their overall knowledge in the computer security area.